Virgin coconut oil protected the diameter and the epithelium thickness of seminiferous tubules of mice (Mus musculus) from oral ethanol induction - S Ravi, Vishantheni; Soeharsono, Soeharsono; Plumeriastuti, Hani; Rachmawati, Kadek (Ovozoa: Journal of Animal Reproduction, 2022)
This study investigated the preventive effect of virgin coconut oil (VCO) on the epithelium thickness and the diameter of the seminiferous tubules induced by ethanol in mice (Mus musculus). This study used 20 male mice as the experimental animal which were divided into five groups with four mice in each group. Negative control (C-) was given 2% Tween and aquadest, while positive control (C+) was given 2% Tween and 33% ethanol. T1, T2, and T3 were respectively given 0.09, 0.19, and 0.37 mL/kg bw VCO and 33% ethanol (0.2 mL/kg bw). VCO was given orally for 39 days, and ethanol was given orally seven days later for 32 days. Ethanol was administered two hours after the VCO administration. Analysis of variance followed by Tukey's range test on the epithelium thickness and the diameter of the seminiferous tubules showed significant differences (p <0.05) of C+ group from the other groups. Whereas, there was no significant difference (p >0.05) was found among C-, T1, T2 and T3 group. The result concluded that VCO could protect the testis of mice from the damage caused by ethanol.